Multipoint Nanolaser Array in an Individual Core–Shell CdS Branched Nanostructure. Issue 11 (29th March 2020) - Hao, Yan; Ding, Chunjie; Lu, Tianqi; Xie, Lingling; Nan, Pengfei; Guo, Shuai; Wang, Xianshuang; Li, Angze; Xu, Xiangjun; Zou, Bingsuo; Liu, Ruibin
Abstract: Nanoscale laser arrays are attractive for their potential applications in highly integrated nanodevices, which are always obtained by nanowire arrays with complicated fabrication techniques. Here, a quite different nanolaser array is successfully realized based on a highly ordered core–shell CdS branched nanostructure with implanted Sn nanoparticles in junctions that split the individual multichannel nanostructures to various microcavities with effective light confinement and oscillation, thus to achieve a multipoint nanolaser array. Under the excitation of an ultraviolet laser, the strong band‐edge emission can be well reflected between Sn nanoparticles at junctions and effectively scattered into branch segments due to Sn nanoparticles existence in junctions, furthermore oscillating in various microcavities along trunks or branches to form multipoint lasing from Fabry‐Pérot (F‐P) mode with a quality factor up to 990 and the low threshold at around 3.78 MW cm −2 . The corresponding fluorescent microscope images further demonstrate the formation of multipoint F‐P lasing at various segments. The theoretical simulation indicates that implanted Sn nanoparticles work as hot point to enhance the confinement of light around the Sn centers. The existence of surface plasmon from the Sn metal particles is further confirmed by the polarization dependent photoluminescence measurement. The results provide a new way to realize nanolaser arrays. Abstract : A multipoint nanolaser array is realized under UV light irradiation from an individual core–shell CdS branched nanostructure with Sn core encapsulated in junctions, where the Sn nanoparticles can act as efficient scattering and reflection centers to divide the nanostructure into several segments to form various microcavities to realize Fabry‐Pérot lasing with the highest Q factor up to 990.